ACTIVATION OF EDUCATIONAL AND EDUCATIONAL ACTIVITIES OF STUDENTS - E. Gazizova, S.; R. Gazizov, E.; G. Kiseleva, N.; N. Zinnatullina, A. (Gênero & Direito, 2019)
Students’ activity in educational activities depends on their interest in learning. Students’ interest in the subject is associated with an understanding of its significance for the future profession. To interest a student in a subject under study is a rather complicated process. For the interconnected activities of the teacher and student, it is necessary to use various teaching methods. Training is a focused pedagogical process that has been designed in advance. The learning process is associated with movement, that is, from the solution of one set educational task, a transition to another occurs, thereby promoting the student along the path of knowledge: the transition from ignorance to knowledge, from incomplete knowledge to a more complete and accurate one. Cognitive interest plays an important role in the student’s activity, emotionally colors all his educational activities. The intensification of educational and cognitive activities of students is aimed at obtaining strong and stable knowledge. To highly motivate the student to gain knowledge, he must have a well-formed image of his future profession. An indicator of the student’s relationship with the subject of his activity is activity. Activation of educational and cognitive activities of students remains the main problem in the educational process. Educational and cognitive activity of students implies the development of independence and creative activity in the learning process. The activity of students implies the awareness of the fulfillment of educational tasks, the systematic nature of training, the desire to increase the level of knowledge and others